2019
DOI: 10.1177/0361198119843091
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Restraint Use and Injury in New York City Taxis Compared with Other Passenger Vehicles

Abstract: In New York City (NYC), as in several other U.S. cities, pediatric occupant restraint laws exempt rear-seated passengers in vehicles-for-hire from those that apply to private vehicles. This study compares rear-seated infant, child, adolescent, and teen passenger restraint use and injury in taxis compared with other passenger vehicles. New York State Department of Health Crash Outcome Data Evaluation System (CODES) was analyzed for rear-seated pediatric passengers aged 0–19 years traveling in taxis ( n = 1,631)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…For example, while 85.6 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint while travelling in their private motor vehicle, only 57.3 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint when they travelled in a rideshare vehicle. These findings are consistent with several studies from the United States who have recently noted that parents restrain their children 'differently' while travelling in alternative transport modes such as rideshare vehicles [6,19], taxis [16,18], or carpooling [17]. These findings have significant implications, suggesting that child occupants may be at an increased risk of death or serious injury in the event of a motor vehicle crash while travelling in these modes of transport.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, while 85.6 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint while travelling in their private motor vehicle, only 57.3 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint when they travelled in a rideshare vehicle. These findings are consistent with several studies from the United States who have recently noted that parents restrain their children 'differently' while travelling in alternative transport modes such as rideshare vehicles [6,19], taxis [16,18], or carpooling [17]. These findings have significant implications, suggesting that child occupants may be at an increased risk of death or serious injury in the event of a motor vehicle crash while travelling in these modes of transport.…”
Section: Discussionsupporting
confidence: 90%
“…Although child restraint use is high (i.e., over 90%) in private motor vehicles in Australia [13][14][15], research has shown that child restraint use is substantially lower in shared transportation modes such as taxis, rideshare vehicles and carpooling [6,[16][17][18][19]. For example, in the United States, Owens and colleagues [6] reported that 59 percent of parents restrained their children aged five years and younger 'differently' when travelling in a rideshare vehicle than they did when travelling in their private motor vehicle, including holding the child on their lap (37.0%) or letting their child travel without an appropriate child restraint (25.0%).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to link could have underestimated the incidence of injury in this study population, but crashes that linked had high fidelity. Vehicles for hire have been shown to have lower overall restraint use and higher injury rates among children compared to private vehicles (Prince et al, 2019 ). This analysis did not differentiate between privately-owned vehicles and vehicles for hire such as taxi cabs, Uber, Lyft, and other ride-share modes of transit.…”
Section: Discussionmentioning
confidence: 99%
“…The fruits of this ongoing academic-practice partnership—which yielded important, actionable data—helped to raise the profile of this injury issue among injury prevention professionals, policymakers, and residents and visitors. It also stimulated the co-writing of a grant to support further analysis of CODES in aging and frail adult populations, a conference on rear-seat safety, a webinar 29 , a scientific meeting abstract, and forthcoming peer-reviewed manuscripts 30 coauthored by the NYSDOH and CU-ICRC collaborators. Additionally, the NYSDOH/CU-ICRC academic-practice partnership provided a training opportunity for interns, strengthened scientific collaborations through use of diverse perspectives, and increased access to the CODES database to narrow scientific gaps and strengthen evidence-based public messaging around rear seat passenger safety.…”
Section: Case Examplesmentioning
confidence: 99%